Influence of land use on carbon storage in productive systems and primary forest in Napo, Sumaco Biosphere Reserve, Ecuador - Jadán, Oswaldo (2012)
Despite growing evidence of the effect of traditional production systems on carbon sequestration and storage, little research has been conducted to examine the relationship between forest and traditional production systems based on the mitigation of climate change, especially in Amazonian ecosystems. This research was conducted in the lower area of the Sumaco Biosphere Reserve, in the province of Napo, Ecuadorian Amazon. We determined the average storage of carbon (C) in biomass and soil, in seven land use systems: Primary forest, traditional agro forestry systems (chakra) based on the cultivation of cocoa (shade-grown) propagated by seed and grafting cocoa monoculture propagated by seed and by grafts, and chakras without cacao and without shade. As a result, agricultural systems studied with the cocoa agro forestry system propagated by seed is the productive ecosystem that stores the most carbon with an average of 141.4 Mg C ha-1; a relatively high quantity when compared with primary forest sequestration averages of 334 Mg C ha-1 in the same area. The component with the greatest contribution to carbon storage in the forest is the live biomass with 79.1%, and in agricultural systems it is the soil, with ranges of 48.9 to 90.2%.